Equipment selection with heterogeneous fleets for multiple-period schedules - Burt, Christina; Caccetta, Louis; Welgama, P.; Fouche, L. (Palgrave MacMillan, 2011)
In a simple surface mining scenario we consider a mine to have one mining location and dumpsite connected by a truck route. We determine a purchase and salvage policy for trucks and loaders, which minimises the cost of materials handling over a multiple period schedule. This problem becomes large scale when we consider large sets of equipment and long schedules. Pre-existing equipment can lead to heterogeneous fleets; non-uniformity in the operating cost function coupled with compatibility issues also adds to the complexity of the problem. We present an integer programme for this problem, where we introduce a specialised linear constraint set to ensure satisfaction of production requirements while accounting for equipment compatibility. Many aspects of the presented model, such as the consideration of multiple periods and pre-existing equipment, are novel for the mining industry and ensure that the model is both a new and advanced equipment selection tool.